Analysis of Agricultural Loan Use Decision among Poultry Farmers in Oyo State, Nigeria - A.O. , Otunaiya; Ologbon, O.A.C; Akerele, E.O. (International Journal of Poultry Science, 2014)
This study examined the use of agricultural loan among poultry farmers in Lagelu Local Government Area of Oyo state, Nigeria. The study was based on primary data obtained in a cross-section survey of 107 respondents drawn by multi-stage random sampling technique. The study data was analyzed by both descriptive and quantitative techniques. The study revealed that majority of the respondents is still in their active age, though, 88.8% of the poultry farmers are males. Almost all the respondents were married and educated. The result of the logit regression model specified revealed that factors such as gender, household size, amount of credit available, main occupation of the farmer and access to extension agents are the determinants of poultry farmers’ decision to use credit. The analysis of determinants of volume of loan poultry farmers use, using Tobit regression, reveals that factors such as net farm income, market source and gender of the farmers are significant. The study, therefore, recommends that discriminating interest rate that will be female friendly should be introduced by agricultural loan provider to enhance female poultry farmers’ decision for agricultural loans.